Comparison Of Feat Examination Results Using Direct Slide And Sedimentation Methods For Detecting Soil Transmidet Helmint (STH) Worm Infection In Primary School Students - Kahfi Aulia; Rahmadani Sitepu (Institut Kesehatan Medistra Lubuk Pakam, 2023)
The worms are parasitic infections that occur frequently and are estimated to infect 1-45 billion individuals worldwide. There are several types of worms that infect humans, namely roundworms (Ascaris lumbricoides), whipworms (Trichuris trichura), and hookworms or hookworms (Ancylostoma duodenale and necator americanus). The method used in this research is descriptive analytical method, which is the method used to view the description of the examination results from a sample. The population of this study was elementary school students with a sample of 50 students. Based on the results of the study using the direct slide method, negative results were obtained with a percentage of 100% with a total frequency of 50 students. If using the sedimentation method, 3 students were infected with Ascaris lumbrichoides with a percentage of 6.0% and 47 students were not infected with a percentage of 94.0% with a total sample of 50 students. Based on the results of the research using the direct slide and sedimentation methods, the results showed that the results of the two methods used were influenced by different sensitivity.